Experimental analyses of two‐body wave energy converters with hydraulic power take‐off damping in regular and irregular waves. Issue 14 (3rd June 2021) - Wu, Shuang; Liu, Yanjun; Qin, Jian
Abstract: A flume experimental study of a two‐body wave energy converter (WEC) with a hydraulic power take‐off (PTO) was conducted under the conditions of both regular and irregular waves. The experimental results were analysed using the control variable method, and the effects of the wave elements and external load on the relative heave motion response and capture width ratio of the device are discussed. For the regular waves, three modes were found when analysing the variation of the relative heave motion response with the incident wave height, and the initial moving line of the WEC model was obtained. For the irregular waves, the experiment displayed two motion states. One was a following motion with a similar value to the incident wave period, and the other was a delayed motion with a larger value than the wave period. Based on the calculation of the capture width ratio of the system both under the regular and irregular wave conditions, the maximum value occurred at a frequency ratio of ω / ω n = 0.59 and a hydraulic load of p  = 0.20. The capture width ratio in the irregular waves was approximately 10%‐40% higher than that of the regular waves for the same wave parameters.